Formation of Global Competence of the Future Primary School Teacher - Damirovna, Kodirova Feruza (European Journal of Life Safety and Stability (2660-9630), 2021)
This article presents tactical and strategic issues of the formation of the global competence of a future primary school teacher, identifies the direction, organizational forms and methods of training future teachers.